The re-analysis of the relationship between government's income and expenditure in an oil-based economy with TVPFAVAR approach (Iran as the case of study) - Akbari, Jaber; Bakhtiari, Sadegh; Sameti, Morteza; Ranjbar, Homayoun (International Journal of Energy Economics and Policy, 2017)
Oil incomes play important roles in the budget structure and government expenditures of oil-dependent economies. The existence of such an economic structure has made the causal relationship between government's incomes and expenditures a debatable issue for economic decision-makers. In the previous studies, the relationship between the two variables of Iran's incomes and expenditures was considered linearly, while the nature of these two variables is non-linear. Due to the limitations of econometric techniques, the non-linear investigation of these variables has not been carried out thus far. Models with changeable parameters over time have solved this problem. So in the present study by applying TVP FAVAR method in MATLAB software and employing seasonal data from 1989 to 2015, attempt has been made to accurately explore the relationship between government's incomes and expenditures. The results of the study demonstrated that the coefficients of income - expenditure over time have a non-linear fluctuation mode. Therefore, simultaneous fiscal policy hypothesis is confirmed for Iran. Keywords: Oil shocks, income – expenditure relationship, government, TVP-FAVAR JEL Classifications: C13, C18, H50, H20,